The Velocity of Circulation of Goods: An Explanation - Lounsbury, Raymond H. (Quarterly Journal of Economics, 1934)
Journal Article The Velocity of Circulation of Goods: An Explanation Get access Raymond H. Lounsbury Raymond H. Lounsbury University of Illinois Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 48, Issue 4, August 1934, Pages 767–768, https://doi.org/10.2307/1883553 Published: 01 August 1934